EZH2 T367 phosphorylation activates p38 signaling through lysine methylation to promote breast cancer progression - Maria E. Gonzalez; Giuseppina Daniela Naimo; Talha Anwar; Alessandro Paolì; Shilpa R. Tekula; Suny Kim; Natasha Medhora; Shoshana A. Leflein; Jacob Itkin; Raymond Trievel; Kelley M. Kidwell; Yu-Chih Chen; et al. (iScience, 2022)
Summary: Triple-negative breast cancers (TNBCs) are frequently poorly differentiated with high propensity for metastasis. Enhancer of zeste homolog 2 (EZH2) is the lysine methyltransferase of polycomb repressive complex 2 that mediates transcriptional repression in normal cells and in cancer through H3K27me3. However, H3K27me3-independent non-canonical functions of EZH2 are incompletely understood. We reported that EZH2 phosphorylation at T367 by p38α induces TNBC metastasis in an H3K27me3-independent manner. Here, we show that cytosolic EZH2 methylates p38α at lysine 139 and 165 leading to enhanced p38α stability and that p38 methylation and activation require T367 phosphorylation of EZH2. Dual inhibition of EZH2 methyltransferase and p38 kinase activities downregulates pEZH2-T367, H3K27me3, and p-p38 pathways in vivo and reduces TNBC growth and metastasis. These data uncover a cooperation between EZH2 canonical and non-canonical mechanisms and suggest that inhibition of these pathways may be a potential therapeutic strategy.